Teachers’ conceptions of standards in South African Basic Education and Training: a case study - Sosibo, Lungi; Nomlomo, Vuyokazi (Faculty of Education, University of the Free State, 2014)
In South Africa, the Department of Basic Education and Training (DBE) is responsible for primary and secondary education (Grades R-12). In an effort to improve educational standards in literacy, numeracy and mathematics, especially in the Foundation Phase (FP) levels of education, the DBE has developed several initiatives and campaigns. To monitor the standards and set targets, the department administers high-stakes standardised tests similar to those conducted in the United States of America (USA) at elementary and secondary schools. In spite of these efforts, the national low performance levels of Grades R-12 remain a grave social concern. This study investigated the conceptions of standards from a purposive sample of twenty elementary school teachers selected from three Cape Town schools, with the objective of establishing how their understandings of standards influenced their classroom pedagogical practices. Activity theory informed this research. Data were collected through focus group semi-structured interviews. Results showed that teachers perceived the disadvantaged contexts in which they function as limiting their pedagogical practices and availability of socio-cultural artefacts that they need, thus preventing them from achieving their objectives of maintaining good educational standards. Evidently, the lack of a clear definition of standards, and teachers’ exclusion from participation in the standards-setting processes appear to restrict their understanding of standards and, by implication, their classroom practices and activities aimed at promoting standards. We conclude that a lack of clarity on the definition of standards for FP teachers has detrimental effects on their classroom practices as they function in diverse educational environments.
Keywords: Context; Educational standards; Artifacts; Improvement; Practices; Department of Basic Education and Training